2009
DOI: 10.1051/epjap/2009087
|View full text |Cite
|
Sign up to set email alerts
|

Impedance model for the polarization-dependent optical absorption of superconducting single-photon detectors

Abstract: Abstract.We measured the single-photon detection efficiency of NbN superconducting single-photon detectors as a function of the polarization state of the incident light for different wavelengths in the range from 488 nm to 1550 nm. The polarization contrast varies from ∼5% at 488 nm to ∼30% at 1550 nm, in good agreement with numerical calculations. We use an optical-impedance model to describe the absorption for polarization parallel to the wires of the detector. For the extremely lossy NbN material, the absor… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
56
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(62 citation statements)
references
References 22 publications
6
56
0
Order By: Relevance
“…Using this technique, we achieve selective illumination of either the sides or the middle of the wire, which we use to probe the intrinsic photodetection properties of our device on the nanoscale. However, it is well known that changing the polarization results in a change in overall optical absorption probability [16][17][18][19][20]. In order to correct for this effect, we must separate the probability that a photon is absorbed from the probability that an absorbed photon causes a detection event.…”
mentioning
confidence: 99%
“…Using this technique, we achieve selective illumination of either the sides or the middle of the wire, which we use to probe the intrinsic photodetection properties of our device on the nanoscale. However, it is well known that changing the polarization results in a change in overall optical absorption probability [16][17][18][19][20]. In order to correct for this effect, we must separate the probability that a photon is absorbed from the probability that an absorbed photon causes a detection event.…”
mentioning
confidence: 99%
“…As can be seen in the figure, the internal detection efficiency of meandering wires is proportional to the fill fraction f , defined as the ratio of wire width w over the pitch p. Numerical calculations of the absorption profile of the various structures indeed show that the absorption distribution A ⊥, (x) is nearly identical to that of an isolated wire, resulting in an average absorption η that is proportional to f [27]. For a wavelength of 1550 nm the IDE of the SSPDs (slope of the dashed line) with parallel polarization is higher than that of SSPDs with perpendicular polarization, which is explained by the difference in absorption profile A ⊥, (x) for the two polarizations.…”
Section: A Optimal Response Of Meandering Wire Detectorsmentioning
confidence: 80%
“…As can be seen in the figure, the internal detection efficiency of meandering wires is proportional to the fill fraction f, defined as the ratio of the wire width w over the pitch p. Numerical calculations of the absorption profile of the various structures indeed show that the absorption distribution A ⊥;∥ ðxÞ is nearly identical to that of an isolated wire, resulting in an average absorption η that is proportional to f [27]. For a wavelength of 1550 nm, the IDE of the SSPDs (the slope of the dashed line) with parallel polarization is higher than that of SSPDs with perpendicular polarization, which is explained by the difference in absorption profile A ⊥;∥ ðxÞ for the two polarizations.…”
Section: A Optimal Response Of Meandering Wire Detectorsmentioning
confidence: 82%
“…A known limitation of (meandering) wires is that the detection efficiency depends on the polarization of the incident light [26,27]; at normal incidence, absorption is more efficient when the electrical field vector of the light is aligned parallel to the wires, an effect governed by the boundary conditions on the edges of the nanowires. Recently, a design of a cavity-based structure was reported that tries to eliminate the polarization dependence and achieves up to 96% absorption efficiency for both polarizations [28], assuming that the internal detection efficiency is uniform across the nanowire.…”
Section: Local Detection Efficiencymentioning
confidence: 99%